Improving Students’ Ability in Writing Descriptive Text Through Contextual Teaching and Learning Approach - Windi Windi; Maman Suryaman (Jurnal Ilmiah Profesi Pendidikan, 2022)
Contextual Teaching and Learning Approach is a holistic educational process that aims to motivate students to understand the meaning of the subject matter being studied by connecting the material to the context of their daily lives so that students have knowledge/skills that can be flexibly applied (transferred) from one problem/context to another. This study aims to determine the improvement students' ability in writing descriptive texts through CTL and the advantages of using the CTL approach. Contextual Teaching and Learning techniques to teach descriptive writing is proven to be helpful in increasing student progress. Therefore, this study uses a qualitative research approach as a research strategy, so a literature review will be used. Based on these data, the training approach is effective in developing descriptive text writing skills, with the results of the activities covering library data collection methods, reading and taking notes, and material management. The results of this study reveal a number of advantages of CTL. This includes, involving students in writing activities; improve students' enthusiasm to engage actively in writing classes; assist students in constructing their writing; assist students in problem solving; give a venue for students to communicate or discuss with their classmates; and assist students in summarizing and reflecting on lesson content. it can be concluded that The contextual approach is a very appropriate vehicle for teachers to empower the potential of students according to the needs and the school environment and their lives. According to these findings, it is suggested the CTLcan be used in the classroom to improve students' descriptive text writing skills.